2021
DOI: 10.1002/hbm.25411
|View full text |Cite
|
Sign up to set email alerts
|

Reduced network integration in default mode and executive networks is associated with social and personal optimism biases

Abstract: An optimism bias refers to the belief in good things happening to oneself in the future with a higher likelihood than is justified. Social optimism biases extend this concept to groups that one identifies with. Previous literature has found that both personal and social optimism biases are linked to brain structure and task‐related brain function. Less is known about whether optimism biases are also expressed in resting‐state functional connectivity (RSFC). Forty‐two participants completed questionnaires on di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
32
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(40 citation statements)
references
References 48 publications
7
32
1
Order By: Relevance
“…Affective cognition has been shown to change throughout the lifespan, with older adults reporting improvement in emotional experience and an increased frequency of positive feelings, relative to younger adults [ 53 ], which is also what we report (see Supplementary Table 4 ). Other neuroimaging studies have independently reported association between affective cognition and working memory network activation [ 7 ], functional network connectivity [ 8 , 13 , 54 , 55 ] or structural morphometry [ 9 ]. It is also known from psychiatric studies that the activation of the working memory network is modulated by the level of depression and anxiety [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Affective cognition has been shown to change throughout the lifespan, with older adults reporting improvement in emotional experience and an increased frequency of positive feelings, relative to younger adults [ 53 ], which is also what we report (see Supplementary Table 4 ). Other neuroimaging studies have independently reported association between affective cognition and working memory network activation [ 7 ], functional network connectivity [ 8 , 13 , 54 , 55 ] or structural morphometry [ 9 ]. It is also known from psychiatric studies that the activation of the working memory network is modulated by the level of depression and anxiety [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…To achieve this, the algorithm groups variables from either side into component pairs/dimensions, which are referred to as modes in the present paper. Instead of a classic (non-sparse) canonical correlation analysis, we conducted sCCA because this analysis (a) permits the inclusion of more features than observations and (b) allows stronger inferences regarding the contribution of individual variables (for similar approaches, see [ 7 , 9 , 55 ]; also see reviews by Zhuang et al [ 36 ], Wang, Smallwood [ 94 ]).…”
Section: Methodsmentioning
confidence: 99%
“…Participants: Our study takes leverage from Moser et al [3], who investigated functional brain correlates of optimism biases. We have used the same dataset in terms of participants, experimental setup, and deriving the optimism biases.…”
Section: Methodsmentioning
confidence: 99%
“…Optimism bias (OB) is a well-established behavioral dimension, where individuals associate themselves with more positive outcome scenarios than negative [1,2]. More specifically, optimism bias can further be branched into the deeper concepts of personal and social optimism biases [3]. Personal optimism bias (POB) stems from a bias towards oneself where an individual expects a more favorable outcome compared to a peer or competitor, given the same scenario.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation